A Systematic Review of Effects of Social Stories Interventions for Individuals With Autism Spectrum Disorder. (March 2018) - Qi, Cathy H.; Barton, Erin E.; Collier, Margo; Lin, Yi-Ling; Montoya, Charisse
The purpose of this systematic review was to synthesize 22 single-case research design (SCRD) studies on social stories intervention for individuals with autism spectrum disorder (ASD). We used the What Works Clearinghouse (WWC) SCRD standards to analyze study rigor and evidence of a causal relation. We calculated four nonoverlap indices to evaluate intervention, maintenance, and generalization effects. Results suggested that all studies met the WWC design standards with or without reservations. Seven studies (32%) provided strong or moderate evidence of a causal relation. Nonoverlap indices calculations indicated social stories intervention was effective. Using the WWC 5-3-20 guidelines to determine evidence of social stories, social stories intervention would not be considered an evidence-based practice (EBP) for individuals with ASD based on visual analysis, but would be deemed an EBP based on nonoverlap indices. It is worth noting that WWC used visual analysis, not nonoveralap indices, to determine whether an intervention meets the 5-3-20 replication rule. Findings of the systematic review showed there were discrepancies. Implications for future research and practice are discussed.